Trustworthy Autonomic Computing - Eze, Thaddeus (Computing and Networks Ser., 2023)
This book covers challenges and solutions of autonomic computing trustworthiness from methods and techniques to achieve consistent and reliable system self-management. This is an ideal tutorial guide for independent study with simple and well documented diagrams to explain techniques and processes.